Effects of acute progesterone administration upon responses to acute psychosocial stress in men - Childs, Emma (Exp Clin Psychopharmacol, 2010)
Animal studies suggest that neuroactive steroids, in particular progesterone and its metabolites, have stress-dampening effects. However, few studies have explored these effects in humans. In this study, we investigated the effects of acute progesterone administration upon responses to the Trier Social Stress Test (TSST). Healthy men participated in the TSST 3.5h after intramuscular injection of 0, 50 or 100mg progesterone (N=16, 14 and 14). We measured cardiovascular (heart rate, blood pressure), hormonal (plasma adrenocorticotrophic hormone, cortisol and noradrenaline) and subjective (e.g. anxiety, arousal) responses to stress in the three groups. Before the TSST, progesterone injections increased plasma levels without altering physiological or subjective states. Stress produced its expected physiological and subjective effects among placebo-treated individuals. Progesterone 50mg attenuated peak increases in plasma cortisol and reduced changes in negative mood and alertness after stress, yet it increased plasma noradrenaline and systolic blood pressure. Progesterone 100mg also attenuated stress-induced increases in alertness and arousal yet it potentiated stress-induced increases in diastolic pressure. Thus, progesterone dampened some of the psychological effects of stress but produced inconsistent effects upon physiological stress responses.